Gross Morphological Studies on the Stomach of Albino Rat (Rattus norvegicus) - Chandana, G. S. S.; Kishore, P. V. S.; Raju, N. K. B.; Sreenu, M.; Rao, G. Srinivasa (Indian Journal of Veterinary Anatomy, 2016)
The ‘C’ shaped stomach of albino rat located in the left parachondriac region of the abdominal cavity was divided into the nonglandular and glandular regions separated by a limiting ridge. The nonglandular left region, the forestomach comprised about 65% whereas the glandular right region constituted about 35% of the total volume of the stomach. The mean length of the nonglandular region was 6.1cm whereas that of the glandular region was 3.9cm when measured along the greater curvature.